2008
DOI: 10.1111/j.1365-2249.2008.03617.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of interleukin 6 in recently hospitalized tick-borne encephalitis patients correlate with age, but not with disease outcome

Abstract: SummaryInfection with many encephalitic viruses is associated with the induction of the proinflammatory cytokine interleukin (IL)-6. In some situations, induction of high levels of this cytokine is associated with a protective response, but in others it can be linked to tissue damage and disease. In the studies reported here, levels of serum IL-6 and virus-specific antibodies were measured on admission to hospital and correlated with clinical outcomes. Only some patients demonstrated raised levels of serum IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
(28 reference statements)
1
8
1
3
Order By: Relevance
“…Interestingly, pediatric TBE patients displayed the highest levels of serum IL-6 at admission, but did not manifest symptoms of meningitis or meningoencephalitis, as the adults did [Atrasheuskaya et al, 2003]. Another study demonstrated that only some TBE patients harbored elevated serum levels of IL-6; these levels correlated with age, but not with gender or disease outcome [Toporkova et al, 2008]. No correlation between serum IL-6 levels and age was detected in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…Interestingly, pediatric TBE patients displayed the highest levels of serum IL-6 at admission, but did not manifest symptoms of meningitis or meningoencephalitis, as the adults did [Atrasheuskaya et al, 2003]. Another study demonstrated that only some TBE patients harbored elevated serum levels of IL-6; these levels correlated with age, but not with gender or disease outcome [Toporkova et al, 2008]. No correlation between serum IL-6 levels and age was detected in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…The overall figures for Russia also suggest a similar trend, although the numbers of cases are still in the thousands ( Fig. 1) and in one region of Russia alone (Eikatherinburg, Ural region), there are 300-500 reported cases every year (Toporkova et al, 2008). Within Russia, western Siberia has the highest incidence of TBE cases in the world (10 298 cases in 1996), although the apparent yearly decrease to 3098 cases in 2007 cannot be attributed to vaccination alone (Süss, 2008).…”
Section: Introductionmentioning
confidence: 59%
“…Haematogenic spread allows different organs to be infected, especially the reticulo-endothelial system (spleen, liver and bone marrow) (Haglund & Günther, 2003), and it is during this phase that the virus also crosses the blood-brain barrier to invade the central nervous system (CNS), where viral replication causes inflammation, lysis and cellular dysfunction (Dumpis et al, 1999). Neuroinvasion of TBEV in humans has been well reported, although the mechanisms by which an acute, non-fatal febrile infection develops into a severe, possibly fatal CNS disease are not clearly understood (Toporkova et al, 2008).…”
Section: Pathogenesismentioning
confidence: 99%
“…IL-1α and TNF-α act synergistically to initiate the cascade of inflammatory mediators by targeting the endothelium. Thus, increased brain production of IL-6, TNF-α and IL-1α/β may explain the observed inflammatory response, neuronal damage, meningitis, meningioencephalitis and meningioencephalomyelitis evident during RSSEV infection (Gunther et al, 1997; Toporkova et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…The innate and adaptive immune responses, with special reference to the cytokine profile, during OHFV or RSSEV infection is largely unknown. However, it has been reported that various proinflammatory mediators such as TNF-α, IL-1α and IL-6 were elevated in human TBE patients (Atrasheuskaya et al, 2003; Kondrusik et al, 2001; Timofeev et al, 2002; Toporkova et al, 2008). The decline of these proinflammatory cytokines together with an elevation of IL-10 was also associated with recovery (Atrasheuskaya et al, 2003; Kondrusik et al, 2001).…”
Section: Introductionmentioning
confidence: 99%